A traditional Chinese formula composed of Chuanxiong Rhizoma and Gastrodiae Rhizoma (Da Chuanxiong Formula) suppresses inflammatory response in LPS -induced RAW 264.7 cells through inhibition of NF-κB pathway. (20th January 2017) - Liu, Zhi-Ke; Ng, Chun-Fai; Shiu, Hoi-Ting; Wong, Hing-Lok; Wong, Chun-Wai; Li, Kai-Kai; Zhang, Jin-Fang; Lam, Ping-Kuen; Poon, Wai-Sang; Lau, Clara Bik-San; Leung, Ping-Chung; Ko, Chun-Hay
Abstract: Ethnopharmacological relevance: Da Chuanxiong Formula (DCXF) which origins from Jin Dynasty is a famous classical 2-herb Chinese medicinal prescription. It is composed of dried rhizomes of Ligusticum chuanxiong (Chuanxiong Rhizoma, CR) and Gastrodia elata (Gastrodiae Rhizoma, GR) at the ratio of 4:1 (w/w). It has been used to treat headache which is caused by wind pathogen and blood stasis for thousands of years in China. Aim of study: The present study was performed to investigate the anti-inflammatory effect of DCXF and elucidate its underlying molecular mechanisms using LPS-stimulated RAW 264.7 cells. Materials and methods: The anti-inflammatory effect of DCXF was evaluated using LPS-stimulated RAW 264.7 cells. Generation of nitric oxide (NO) and prostaglandin E2 (PGE2 ) were measured by the Griess colorimetric method and enzyme-linked immunosorbent assay (ELISA), respectively. The gene expressions of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) were detected by reverse transcription-polymerase chain reaction (RT-PCR). Furthermore, the effect of DCXF on NF-κB activation was measured by western blot assay. Results: Treatment with DCXF significantly suppressed the productions of NO and PGE2 through inhibitions of iNOS and COX-2 expressions in LPS-stimulated RAW 264.7 cells. DCXF significantly decreased IκBα phosphorylation, inhibited p65 expression and reduced p-p65 level. These results suggested the anti-inflammatory effect of DCXF was associated with the reduction of inflammatory mediators through inhibition of NF-κB pathway. Conclusions: These results indicated that DCXF inhibited inflammation in LPS-stimulated RAW 264.7 cells through inactivation of NF-κB pathway. Graphical abstract: